2019
DOI: 10.1104/pp.18.01448
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Cold Acclimation and Its Role in Niche Transition in the Temperate Grass Subfamily Pooideae

Abstract: The grass subfamily Pooideae dominates the grass floras in cold temperate regions and has evolved complex physiological adaptations to cope with extreme environmental conditions like frost, winter, and seasonality. One such adaptation is cold acclimation, wherein plants increase their frost tolerance in response to gradually falling temperatures and shorter days in the autumn. However, understanding how complex traits like cold acclimation evolve remains a major challenge in evolutionary biology. Here, we inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 135 publications
13
42
0
Order By: Relevance
“…This observation is also supported by the analysis of the most conserved families operating upon stress (Figs 6d, S9), in which we find several, mostly down-regulated photosynthesis and primary metabolism-related families. Similar trends have been found in grasses, where the various members of the family Pooideae showed highly diverse transcriptomic responses to cold stress, but a common down-regulation of transcripts involved in photosynthesis and metabolism (Schubert et al, 2019). Analysis of photosynthesis parameters during salt stress revealed that this is reflected by a decrease in the total performance index of photosynthesis in multiple species (Pavlovi c et al, 2019), showing a correlation between the transcript responses and plant phenotype.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This observation is also supported by the analysis of the most conserved families operating upon stress (Figs 6d, S9), in which we find several, mostly down-regulated photosynthesis and primary metabolism-related families. Similar trends have been found in grasses, where the various members of the family Pooideae showed highly diverse transcriptomic responses to cold stress, but a common down-regulation of transcripts involved in photosynthesis and metabolism (Schubert et al, 2019). Analysis of photosynthesis parameters during salt stress revealed that this is reflected by a decrease in the total performance index of photosynthesis in multiple species (Pavlovi c et al, 2019), showing a correlation between the transcript responses and plant phenotype.…”
Section: Discussionsupporting
confidence: 70%
“…5d). Similar trends have been found in grasses, where the various members of the family Pooideae showed highly diverse transcriptomic responses to cold stress, but a common down-regulation of transcripts involved in photosynthesis and metabolism (Schubert et al, 2019). Similar trends have been found in grasses, where the various members of the family Pooideae showed highly diverse transcriptomic responses to cold stress, but a common down-regulation of transcripts involved in photosynthesis and metabolism (Schubert et al, 2019).…”
Section: Discussionsupporting
confidence: 69%
“…In a study of three Pooideae species, Zhong, Robbett, Poire, & Preston () identified several gene clusters exhibiting conserved cold response, many of which had previously been characterized as ancient stress response genes. Another study found 16 cold‐responsive genes that exhibited conserved expression in five distantly related Pooideae species (Schubert, Grønvold, Sandve, Hvidsten, & Fjellheim, ). Interestingly, most of these genes were induced in response to short‐term cold and are known to be stress responsive in other angiosperms.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings corroborate recent studies of molecular evolution of cold adaptation. Although all species from distantly related Pooideae lineages are able to acclimatize to cold, most of the cold-responsive genes identified by Schubert et al, (2019) were differentially expressed in only one of five investigated species representing different tribes.…”
Section: Lineage-specific Adaptations To Long Wintersmentioning
confidence: 96%
See 1 more Smart Citation